Township-level governance in disaster preparedness in Yangon, Myanmar, during the period of transformation from April 2011 to January 2021 - Zin Mar Than; Hlaing Maw Oo; Sophie-Bo Heinkel; Toe Aung; Tin Tin Kyi; Saw Sandar Oo; Win Lei Mar; Win Maung; Zin Nwe Myint; Khin Khin Soe; Marlene Willkomm; Christian Miller; et al. (Natural Hazards, 2026)
Since Cyclone Nargis hit the country in 2008, Myanmar has stepped up its efforts to implement a disaster management system aimed at reducing disaster risk. At the same time, a far-reaching political and social transformation took place, shifting from military to civilian administration between April 2011 and January 2021. During this period, new concepts for disaster risk management were developed internationally, focusing on local governance and community-based strategies. This article provides an overview of the legal and organisational framework introduced in Myanmar for disaster risk management during the transition phase. In particular, it examines how and to what extent governance elements have been integrated into the system to meet local societal needs. The focus is on identifying challenges, gaps and opportunities in local governance structures. The study employs a mixed-methods analysis approach. This involved conducting 28 expert interviews with Yangon-based disaster management institution members as well as a quantitative household survey of 896 people in eight Yangon townships. Additionally, an in-depth analysis of government documents and reports was conducted. The study shows that the general framework for implementing governance aspects was already well established when the political system changed again in 2021. In practice, however, governance aspects remain challenging.

Genetic diversity and phylogenetic relationships among western and Asian honey bees, and Eristalis tenax collected in Myanmar - Saw Bawm; Aye Pyae Pyae Khaing; Hlaing Min Oo; Myint Myint Mu; Ngwe Chi Hmuu; Aye Nyein Sandi Zaw; Nyunt Lwin; Hla Myet Chel; Yadanar Khaing; Shwe Yee Win; Lat Lat Htun; Shiro Murata; et al. (Journal of Asia-Pacific Entomology, 2025)

Observed characteristics of flow, water mass, and turbulent mixing in the Preparis Channel - Ruijie Ye; Feng Zhou; Xiao Ma; Dingyong Zeng; Feilong Lin; Hongliang Li; Chenggang Liu; Soe Moe Lwin; Hlaing Swe Win; Soe Pyae Aung (Acta Oceanologica Sinica, 2023)

Political transition and emergent forest‐conservation issues in Myanmar - Graham W. Prescott; William J. Sutherland; Daniel Aguirre; Matthew Baird; Vicky Bowman; Jake Brunner; Grant M. Connette; Martin Cosier; David Dapice; Jose Don T. De Alban; Alex Diment; Julia Fogerite; et al. (Conservation Biology, 2017)
Political and economic transitions have had substantial impacts on forest conservation. Where transitions are underway or anticipated, historical precedent and methods for systematically assessing future trends should be used to anticipate likely threats to forest conservation and design appropriate and prescient policy measures to counteract them. Myanmar is transitioning from an authoritarian, centralized state with a highly regulated economy to a more decentralized and economically liberal democracy and is working to end a long‐running civil war. With these transitions in mind, we used a horizon‐scanning approach to assess the 40 emerging issues most affecting Myanmar's forests, including internal conflict, land‐tenure insecurity, large‐scale agricultural development, demise of state timber enterprises, shortfalls in government revenue and capacity, and opening of new deforestation frontiers with new roads, mines, and hydroelectric dams. Averting these threats will require, for example, overhauling governance models, building capacity, improving infrastructure‐ and energy‐project planning, and reforming land‐tenure and environmental‐protection laws. Although challenges to conservation in Myanmar are daunting, the political transition offers an opportunity for conservationists and researchers to help shape a future that enhances Myanmar's social, economic, and environmental potential while learning and applying lessons from other countries. Our approach and results are relevant to other countries undergoing similar transitions.